Commentary: Education at the Faculty of Medicine - W. F. Maramis (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2016)
In his article entitled Neoliberalism Within Psychology Higher Education in Indonesia: A Critical Analysis (Anima Indonesian Psychological Journal, 32(1), 1-11), the author, Teguh Wijaya Mulya, using a broad, in-depth, and philosophical view, has claimed in the conclusion section that (cited as follows): “In contrast to medical schools that usually approach humans as a collection of interconnected organs that may or may not function properly, psychology (cl)aims to engage with humans as humans”. I would like to comment on this statement.